MODIFIKASI STRUKTUR PERMUKAAN ALUMINIUM DENGAN BUBUK BESI MENGGUNAKAN METODA MECHANICAL ALLOYING[Surface Modification of Aluminum Plate With Iron Powder using Mechanical Alloying Method] - Wismogroho, Agus Sukarto; Sebleku, Pius (Jurnal Metalurgi, 2013)
In this research, a study on the modification of the surface structure of the aluminum plate with iron powder using the mechanical alloying (MA) methode was conducted. This process aims to obtain a coating layer of alloy between aluminum plates with iron powder used. Aluminum plates, iron powder and milling balls inserted into the milling vessel for the MA process. The amount of iron powder used was 2 and 10 grams. MA was done up to 10 hours. MA results showed that the coating layer of iron particles can be obtained on the surface of the aluminum plate. The microstructure of the coating layers formed a lamellar structure between Al and Fe. With increasing MA time, the iron particles entered the surface of the aluminum plate, while aluminum was pushed out that made the compound or mixing between Fe and Al. In the MA process with 2 grams iron powder, the FeAl phase was obtained after MA for more than 2 hours. While in the process of MA with 10 grams iron powder, a new phase wasn’t observed even though after MA for 10 hours. The coating layers formation of the mixing Fe-Al, the Fe-Al alloy and the formation time were strongly influenced by the amount of iron powder used in the MA process. The optimal coating thickness was about 100μm, with apparently had a high density and a good bond.